The game maker's companion : game development : the journey continues - Habgood, Jacob (Technology in action series., 2010)
The Game Maker's Companion is the long-awaited sequel to The Game Maker's Apprentice. This book picks up where the last book left off, advancing your game development journey with some seriously impressive gaming projects. This time you'll learn how to make professional-quality platform games with solid collision detection and slick control mechanisms and you'll get acquainted with a long-lost icon of platform gaming history on the way. You'll go on to discover techniques to add depth and believability to the characters and stories in your games, including The Monomyth, cut scene storyboarding.